Multiple aperture synthetic optical coherence tomography for biological tissue imaging - Bo, En (2018)
An inherent compromise must be made between transverse resolution and depth of focus (DOF) in spectral domain optical coherence tomography (SD-OCT). Thus far, OCT has not been capable of providing a sufficient DOF to stably acquire cellular-resolution images. We previously reported a novel technique named multiple aperture synthesis (MAS) to extend the DOF in high-resolution OCT [Optica 4, 701 (2017)]. In this technique, the illumination beam is scanned across the objective lens pupil plane by being steered at the pinhole using a custom-made microcylindrical lens. Images captured via multiple distinctive apertures were digitally refocused, which is similar to synthetic aperture radar. In this study, we applied this technique for the first time to image both a homemade microparticle sample and biological tissue. The results demonstrated the feasibility and efficacy of high-resolution biological tissue imaging with a dramatic DOF extension.